Difusi Inovasi Pelayanan Program Angkutan Sekolah Gratis (ASG) di Kota Madiun - Merinda Ulfatiyana (Jurnal Administrasi Publik, 2020)
ABSTRACT The dominance of the use of private vehicles in Madiun often causes traffic jams, especially in the education area at the rush hour. In line with this situation, traffic accidents often occurred especially on a particular lot of students who do not have a driver's license but already drive private vehicles to school. In East Java, the level of traffic accidents and traffic violations are highest in Madiun City, followed by Jember, Jombang. The municipal government of madiun through the department of transportation launched a free school transportation program to suppress accident rates and traffic infraction by students. Free School Transportation Program is an innovation from Madiun City Transportation Agency to provide free school transportation services for students. Therefore, diffusion of innovation or the process of spreading innovation is necessary to raise people's awareness of the Free School Transportation Program. This study aims to determine the diffusion of service innovation for the Free School Transportation Program in Madiun City using 4 (four) important elements of diffusion of innovation by Rogers. The research method is descriptive qualitative method. This research uses in observation, depth interview, and documentation as the data gathering technique, with data sources are informers and documentation. The results of this study indicate that the diffusion of service innovation for the Free School Transportation Program in Madiun City is running quite well and suitable to public service standards.Keywords: Diffusion of Innovation